Atributos de la regeneración natural de ñire (Nothofagus antarctica) en Tierra del Fuego: beneficios y perjuicios que genera el uso silvopastoril - Soler Esteban, Rosina Matilde; Lencinas, María Vanessa; Bustamante, Gimena Noemi; Martínez Pastur, Guillermo José
Seedlings are the early and most fragile phase of the tree’s life. Also, they will define the capacity of forest ecosystem to continue in time and space. Knowledge about the natural regeneration dynamic under silvopastoral management is essential, not only to define the quantity and quality of seedlings, but also to identify which attributes of natural regeneration are benefited and which ones are negatively affected by the silvopastoral use of forests. This work was carried out in ñire (Nothofagus antarctica) forests and the objective was to evaluate the effect of silvopastoral use on forest regeneration (seedling growth, age, origin) over time, and to assess the incidence of different types of damage. We found that the silvopastoral use favors some attributes of ñire regeneration that would allow the maintenance of the tree layer in the future. Among these attributes, a greater probability of seedling survival than unmanaged forests, the presence of resprouting plants with higher growth rate and higher biomass accumulation than seedlings, and the increase of spatial aggregation of seedlings that could be helpful over the livestock impact. However, other attributes were negatively affected by silvopastoral use, e.g., a greater proportion of seedlings damaged by browsing, a lower proportion of seedlings originated by seed which could reduce the genetic diversity in the future, lack of tree regeneration in some sectors of forest floor by aggregation of seedlings in others. We consider that silvopastoral management plans should gear strategies toward minimizing the negative effects of silvopastoral use (e.g., seedling plantation in non-regenerative sectors), and enhancing the positive effects it generates (e.g., thinning to promote the growth of seedlings already installed) to ensure the tree layer maintenance and the ecosystem services it provides. Fil: Soler Esteban, Rosina Matilde. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: ...